Perancangan Ulang Tata Letak Fasilitas Pabrik Menggunakan Metode 5S (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) di PT. Basukigraha Fabrikatama - Aji, Ari Kuntoro; Irwati, Dwi; Najamuddin, Muhammad (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The design of production facilities greatly affects the company's performance because a poor layout can lead to inefficient material flow, increased production costs, and delays in product completion. A good layout in the manufacturing industry is important to maximize area usage and create a smooth flow of materials. Factory layout problems, such as long material movement distances between departments, can affect productivity and profitability. This study aims to minimize material handling costs by determining the best layout. The steps taken include calculating material transfer distances and handling costs in the initial layout, as well as proposing a new layout using the 5S method. After data processing, the initial layout distance previously had a distance of 31.49 m on the proposed layout to 27.63 m and the OHM of the previous initial layout was Rp. 19,213,161.63 per month on the proposed layout to Rp. 16,984,714.11 per month. The results show improvement, with a reduction in material transfer distance and lower monthly handling costs in the proposed layout.